2013
DOI: 10.1152/ajpheart.00634.2012
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal bacteria aggravate experimental autoimmune myocarditis in mice

Abstract: Periodontitis is one of the most common infections in humans. Recently, published reports assert that periodontitis is associated with cardiovascular disease. Although it is said that viral, bacterial infections and autoimmune diseases may be the cause of myocarditis, the pathogenesis of it remains unclear. The aim of this study was to investigate the influence of a periodontal pathogen on experimental autoimmune myocarditis (EAM). Porphyromonas gingivalis (P.g.), PBS as a control, were injected into the mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…This increase was accompanied by a decrease in fractional shortening, suggesting that Pg -LPS exposure induces LV dysfunction through MMP-9 effects on systolic function. This finding is in conflict with findings published in Ashigaki et al, however in this study the exposure to P. gingivalis is only 14 days compared to our study which exposed the mice for 28 days to Pg -LPS (Ashigaki et al 2013). This suggests that longer exposure time may be needed to induce cardiac dysfunction through increased MMP-9.…”
Section: Discussioncontrasting
confidence: 99%
“…This increase was accompanied by a decrease in fractional shortening, suggesting that Pg -LPS exposure induces LV dysfunction through MMP-9 effects on systolic function. This finding is in conflict with findings published in Ashigaki et al, however in this study the exposure to P. gingivalis is only 14 days compared to our study which exposed the mice for 28 days to Pg -LPS (Ashigaki et al 2013). This suggests that longer exposure time may be needed to induce cardiac dysfunction through increased MMP-9.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, despite limitations in clinical research, studies have shown the association between the severity of periodontitis and cardiac hypertrophy in humans 40,41 . Besides, experimental studies with the administration of Porphyromonas gingivalis, one of the major bacteria involved in periodontitis, demonstrated the development of cardiac hypertrophy and fibrosis 42,43 . In addition, in the experimental model of Aggregatibacter actinomycetemcomitans infection, there was also an increase in myocardial hypertrophy, fibrosis, and arteriosclerosis in the transverse aortic constriction model 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Complementary DNA was prepared with a reverse transcriptase-polymerase chain reaction (RT-PCR) kit (QIAGEN, Tokyo, Japan) 27 . The PCR was performed with a PCR-kit in the presence of oligo-primers for transforming growth factor beta 1 ( Tgfb1 , Mm01178820_m1) and collagen1a1 ( Col1a1 , Mm01302043_g1).…”
Section: Methodsmentioning
confidence: 99%